Epstein-Barr virus-transformed B cells, a potentially convenient source of autologous antigen-presenting cells for the propagation of certain human cytotoxic T lymphocytes. - Purner, M B (1994)
Antigen-specific cytotoxic T cells (CTL) are generally elicited in vitro by incubation of effector cells with an appropriate major histocompatibility complex-matched antigen-presenting cell (APC). In the case of CTL derived from inbred rodents, spleen cells from an animal of the same strain serve as a ready source of autologous major histocompatibility complex-identical APC. In outbred human populations, however, a convenient source of human leukocyte antigen-matched APC is ordinarily difficult to obtain, and for that reason human antigen-specific CTL may be difficult to propagate. We describe a method whereby Epstein-Barr virus-transformed human B cells (B-LCL) serve as a convenient source of efficient APC for the propagation of human antigen-specific CTL. B-LCL are produced by using B cells from the donor under study and are thus human leukocyte antigen identical to the donor. Using this method, we have propagated human CD4+ Toxoplasma gondii-specific CTL for up to 9 months in vitro, during which time the cells retained their functional capability.